Experimental and Kinetic Modeling Study of Cyclohexane and Its Mono-alkylated Derivatives Combustion - Wang, Zhandong (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis investigates the combustion chemistry of cyclohexane, methylcyclohexane, and ethylcyclohexane on the basis of state-of-the-art synchrotron radiation photoionization mass spectrometry experiments, quantum chemistry calculations, and extensive kinetic modeling. It explores the initial decomposition mechanism and distribution of the intermediates, proposes a novel formation mechanism of aromatics, and develops a detailed kinetic model to predict the three cycloalkanes' combustion properties under a wide range of conditions. Accordingly, the thesis provides an essential basis for studying much more complex cycloalkanes in transport fuels and has applications in engine and fuel design, as well as emission control.